Systematic studies of the schizaeoid ferns : a taxonomic revision of the genus Mohria Swartz (Anemiaceae) - Roux, J. P.(Jacobus Petrus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1990.